The Effects of Dilute Sulfuric Acid on Sheet Resistance and Transmittance in Poly(3,4-thylenedioxythiophene): Poly(styrenesulfonate) Films - Teen-Hang Meen; Kan-Lin Chen; Yu-Hao Chen; Wen-Ray Chen; Dei-Wei Chou; Wen-How Lan; Chien-Jung Huang (International Journal of Photoenergy)
The conductivity of poly(3,4-thylenedioxythiophene): poly(styrenesulfonate) (PEDOT: PSS) films by adding various molar concentrations of sulfuric acid (H2SO4) was improved and studied in this paper. The sheet resistance of the doped PEDOT: PSS film was enhanced with increasing the ratio of H2SO4, but it drops after the maximum sheet resistance. The reason for this phenomenon is resulting from the fact that the H2SO4 preferentially react with the sorbitol which is so-called the pinacol rearrangement. The nonconductive anions of some PSS− were substituted by the conductive anions of hydrogen sulfate (HSO4-) when the residual H2SO4 reacted with PSS. In addition to the substitution reaction, PEDOT chains were increasingly aggregated with increasing the ratio of H2SO4. After doped H2SO4, the sheet resistance of H2SO4-doped PEDOT: PSS film is improved nearly 36%; the surface roughness is reduced from 1.268 nm to 0.822 nm and the transmittance is up to 91.9% in the visible wavelength range from 400 to 700 nm.